A novel large deletion combined with a nonsense mutation in a Chinese child with Papillon–Lefèvre syndrome. (19th September 2015) - Wu, W.; Chen, B.; Chen, X.; Chen, L.; Yi, L.; Wang, Y.; Yan, F.; Sun, W.
Abstract : Background and objective: Papillon‐Lefèvre Syndrome (PLS) is a rare autosomal recessive hereditary disease (MIM245000). The syndrome is characterized by palmoplantar keratoderma and early onset periodontitis, caused by CTSC gene mutation. The mutation in CTSC previously reported is mainly point mutations. Large deletion in the CTSC gene has not yet been reported. Material and methods: We collected 5 mL peripheral blood from a patient with PLS and her family members and used the direct sequencing method to perform CTSC bidirectional sequencing. We also used FISH to analyze the approximate locations of the ends of the missing fragment and then determined the fragment sequence through direct sequencing. Results: The result demonstrated that the patient have a 110 kb deletion (Chr11: 88032292: 88142997(NC_000011)) combined with a nonsense mutation (Gln182Ter) in this gene. Conclusion: Our study reveals a compound mutation consisting of a large deletion and a nonsense mutation, which provides a new insight in the mutation type of CTSC gene.